Fragmentation of care as a barrier to optimal ESKD management. Issue 6 (31st October 2020) - Sloan, Caroline E.; Zhong, Judy; Mohottige, Dinushika; Hall, Rasheeda; Diamantidis, Clarissa J.; Boulware, Leight E.; Wang, Virginia
Abstract: Caring for patients with end‐stage kidney disease (ESKD) in the United States is challenging, due in part to the complex epidemiology of the disease's progression as well as the ways in which care is delivered. As CKD progresses toward ESKD, the number of comorbidities increases and care involves multiple healthcare providers from multiple subspecialties. This occurs in the context of a fragmented US healthcare delivery system that is traditionally siloed by provider specialty, organization, as well as systems of payment and administration. This article describes the role of care fragmentation in the delivery of optimal ESKD care and identifies research gaps in the evidence across the continuum of care. We then consider the impact of care fragmentation on ESKD care from the patient and health system perspectives and explore opportunities for system‐level interventions aimed at improving care for patients with ESKD.